Thermoreversible in situ gelling formulation of carbamazepine for intranasal delivery : preparation, characterization and ex-vivo study - Keithanchali, Mohananaidu (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2020)
Carbamazepine (CBZ) is used to treat epilepsy and is an anti-convulsant requiring the drug to reach the brain to exert their pharmacological response. The presence of blood-brain barrier (BBB) poses a great challenge for any drugs to reach the receptors in the brain especially when the drugs are administered by oral route. Over the past decade, intranasal (IN) delivery has been increasingly considered as an alternative route of drug delivery. This is because the nasal mucosa has a large surface area and high blood flow that allows better bioavailability. However, this route poses high variability in drug absorption due to short retention time of dosage form on nasal mucosa complicated by naso-ciliary clearance mechanism. This research aims to investigate ability of a novel dosage form i.e. a thermoreversible in situ gelling system on absorption of CBZ via IN route. Briefly, a CBZ thermoreversible gel was developed by mixing 15-20% Poloxamer 407 (P407) with 0.15-0.25% τ-Carrageenan (ɩ-Cg) by cold method to 3% CBZ solution (weight ratio). The formulations takes liquid state when stored at 2-8 ̊ C and gel at nasal temperatures (32-34°С). The gelation temperature and pH for the in situ gels were 26-36 °C and 4.5-6.5 respectively. CBZ compatibility in formulation was determined by a developed ATR-FTIR method. Rheology study of the gel by a controlled (CR) ramp test showed pseudoplasticity and distinct shear-thinning with increasing shear stress. CT3 Texture analyzer was used to determine the mucoadhesion strength of the gel using goat nasal mucosa. Monopolymeric formulations containing 18% and 20% showed greater mucoadhesive strength (<300,000 dyne/cm²) as opposed to binary mixtures containing P407 and ɩ-Cg (T10-T18). In vitro was conducted with a dialysis membrane and formulations containing only P407 had greater release compared to those with both P407 and ɩ-Cg in 24h. Ex-vivo drug permeation study through goat nasal mucosa was done using Franz diffusion cell. Permeation flux was shown to be greater in case of thermoreversible gel without ɩ-Cg. Drug permeation studies have indicated that the permeation decreases with increasing ɩ-Cg concentration. Formulation containing 18% P407 + 0.20% ɩ-Cg showed the highest cumulative drug permeation at 243.94 ug/cm². The gel formula demonstrated high flux and correlated well with the mucoadhesive strength. The use of ɩ-Cg is to ensure prolonged contact of the gel and nasal mucosa. The increasing concentrations of binary mixtures showed sustained-release behavior in in-vitro study. From ex-vitro studies, it can be concluded that the in situ gelling system can result in high nasal epithelial permeation with a sustained-release behavior, which have high potential to successfully deliver drugs systemically for a prolonged period of time. The brain distribution study of the drug using the developed in-situ gel is subjected to future in-vivo study in animal model.